Phylogenomics of African radiation of Praomyini (Muridae: Murinae) rodents: First fully resolved phylogeny, evolutionary history and delimitation of extant genera - Nicolas, Violaine; Mikula, Ondřej; Lavrenchenko, Leonid A; Šumbera, Radim; Bartáková, Veronika; Bryjová, Anna; Meheretu, Yonas; Verheyen, Erik; Missoup, Alain Didier; Lemmon, Alan R; Moriarty Lemmon, Emily; Bryja, Josef (Molecular phylogenetics and evolution, 2021)
The tribe Praomyini is a diversified group including 64 species and eight extant rodent genera. They live in a broad spectrum of habitats across whole sub-Saharan Africa. Members of this tribe are often very abundant, they have a key ecological role in ecosystems, they are hosts of many potentially pathogenic microorganisms and comprise numerous agricultural pests. Although this tribe is well supported by both molecular and morphological data, its intergeneric relationships and the species contents of several genera are not yet fully resolved. Recent molecular data suggest that at least three genera in current sense are paraphyletic. However, in these studies the species sampling was sparse and the resolution of relationships among genera was poor, probably due to a fast radiation of the tribe dated to the Miocene and insufficient amount of genetic data. Here we used genomic scale data (395 nuclear loci = 610,965 bp long alignment and mitogenomes = 14,745 bp) and produced the first fully resolved species tree containing most major lineages of the Praomyini tribe (i.e. all but one currently delimited genera and major intrageneric clades). Results of a fossil-based divergence dating analysis suggest that the radiation started during the Messinian stage (ca. 7 Ma) and was likely linked to a fragmentation of the pan-African Miocene forest. Some lineages remained in the rain forests, while many others adapted to a broad spectrum of new open lowland and montane habitats that appeared at the beginning of Pliocene. Our analyses clearly confirmed the presence of three polyphyletic genera (Praomys, Myomyscus and Mastomys). We review current knowledge of these three genera and suggest corresponding taxonomic changes. To keep genera monophyletic, we propose taxonomic re-arrangements and delimit four new genera. Furthermore, we discovered a new highly divergent genetic lineage of Praomyini in southwestern Ethiopia, which is described as a new species and genus.
Keywords: Ethiopia; Anchored phylogenomics; Late Miocene; Tropical Africa; biologická evoluce; Rodentia; zvířata; Taxonomy; ekosystém; Biological Evolution; Radiation; Ecosystem; Etiopie; Murinae; fylogeneze; Phylogeny; Complete mitochondrial DNA; Animals